KARAKTERISTIK DEMOGRAFI DAN KLINIKOPATOLOGI PASIEN KANKER KOLOREKTAL USIA LANJUT - , SARAH MUHAROMAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Colorectal cancer is one of the major causes of morbidity and mortality throughout the world where the highest incidence occurs in the elderly. In developed countries a sharp increase in the incidence of colorectal cancers occur in patients aged over 50 years and only 3% of cases are found in people under 40 years old. It is the same as in Indonesia, where the number of colorectal cancer patients over the age of 40 years to reach 71,83 percent. Objective: To determine the demographic and clinico-pathological characteristics of colorectal cancer in elderly patients. Methods: This is a retrospective study of all elderly patienst diagnosed to have CRC at Dr.Sardjito âTulipâ Cancer Centre in Jogjakarta from 2007 to 2011. The data collected from medical records includes age, gender, financial systems, occupation, level of education, reason for visit, tumor stage and grade, performance status, metastatic status, comorbidity, histology type of tumor, first diagnostic tools, site of the tumor, early symptoms, chief complaints, type of surgery, the first chemotherapy regimen, and theraphy setting. Results: A total of 92 patients were included over 5 year period. The average age at diagnosis was 70,49 years (S.D.=5,020), with 53,3% in the 65-69 years age range, 60,9% of the patients were male. Seventy-two point seven percent of the patients use insurance with 97,4% of the patients come as referral case. The most common histology type is adenocarcinoma NOS (94,4%). Rectal cancer constituted 44,7% of all CRC tumors in this study. Conclusion: This study showed high prevalence of colorectal cancer in 65-69 years old with an increased incidence every year. This data demonstrates the importance of screening program to be implemented for population over the age of 50 years to prevent colorectal cancer in the future.